The Influence of Digital Leadership, Digital Business Model Development, and Digital Service Quality on Purchase Decisions with Technology Readiness as a Moderation Variable - Muhammad Junaid Kamaruddin; Harisuddin (Economic, Management, Business and Accountancy International Journal, 2026)
The rapid growth of e-commerce has encouraged companies to optimize digitalstrategies to enhance consumer purchase decisions. This study examines the effects ofdigital leadership, digital business model development, and digital service quality onpurchase decisions, with technology readiness as a moderating variable among younge-commerce consumers in Indonesia. A quantitative approach was employed usingdata from 100 purposively selected respondents, analyzed through StructuralEquation Modeling (SEM). The results indicate that digital service quality andtechnology readiness have a positive and significant effect on purchase decisions,whereas digital leadership, digital business model development, and the moderatingeffect of technology readiness are not significant. These findings suggest thatpurchase decisions are influenced more by digital service quality and consumers'technology readiness than by firms' internal strategic factors